Participative Planning for Regional Development Performance: Special Region of Yogyakarta Case Study - Tohom, Andilo; Rustiadi, Ernan; Juanda, Bambang; Kinseng , Rilus (International Journal of Scientific Research and Management (IJSRM), 2021)
Abstract. Objectives of this study is to describe a typology of participative planning that has good development performance. This study used the result of my previous study that develop quantitative indicators of participative planning and its alignment with spatial, development, and budget planning. In this study, qualitative research was carried out to deepen and expand the results of the research, using the multi value method of Qualitative Comparative Analysis (mvQCA) and cluster analysis. Qualitative data analysis was carried out in order to produce a participatory planning typology that takes into account the alignment of spatial planning, programs and budgeting. The results of the study, show that information technology-based planning is a participatory planning typology that produces good infrastructure and house settlement performance. The results of this study imply that in order to increase community participation and the alignment role of planning in improving regional development performance. the application of participative planning must be based on information technology. This research is expected to enrich the research methods and measurement methods used on similar topics.